Review of Leda Papastefanaki and Nikos Potamianos, eds., Labour History in the Semi-Periphery: Southern Europe, 19th-20th Centuries - Hantzaroula, Pothiti (Historein, 2023)
Review of Leda Papastefanaki and Nikos Potamianos, eds., Labour History in the Semi-Periphery: Southern Europe, 19th–20th Centuries. Oldenbourg: De Gruyter, 2021. 375 pp.